2019
DOI: 10.1002/slct.201903249
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Induction on the Ultrafast Event of Excited State Proton Transfer Can Probe Its Mechanism

Abstract: When protonic motion is explained as a purely quantum mechanical phenomenon, two extreme situations can be visualized as either the adiabatic or the nonadiabatic limit of proton transfer (PT). Strong orbital coupling between the donor and the acceptor pair in the proton transfer step drives PT mechanism in the adiabatic limit whereas in nonadiabatic limit PT predominantly occurs through tunneling. Here we proposed a unique way to experimentally observe the adiabaticity of PT by introducing chirality in the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The divergent emission spectra of DHHC in water may be due to its photoacidic character, where water molecules act as a base to extract acidic protons of phenolic hydrogen (O27−H36) and form hydronium ions (H 3 O + ). Consequently, the hydronium ion (H 3 O + ) generated during the photoexcitation of DHHC may undergo a solvent‐assisted ESPT process leading to the formation of the keto‐tautomer in the excited state (Scheme 2), which exhibits an emission maximum at 430 nm [24,26,48–51] . However, this phenomenon has not been observed in solvents such as alcohols, suggesting weak acidic nature of photoexcited DHHC [52] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The divergent emission spectra of DHHC in water may be due to its photoacidic character, where water molecules act as a base to extract acidic protons of phenolic hydrogen (O27−H36) and form hydronium ions (H 3 O + ). Consequently, the hydronium ion (H 3 O + ) generated during the photoexcitation of DHHC may undergo a solvent‐assisted ESPT process leading to the formation of the keto‐tautomer in the excited state (Scheme 2), which exhibits an emission maximum at 430 nm [24,26,48–51] . However, this phenomenon has not been observed in solvents such as alcohols, suggesting weak acidic nature of photoexcited DHHC [52] .…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the hydronium ion (H 3 O + ) generated during the photoexcitation of DHHC may undergo a solvent-assisted ESPT process leading to the formation of the keto-tautomer in the excited state (Scheme 2), which exhibits an emission maximum at 430 nm. [24,26,[48][49][50][51] However, this phenomenon has not been observed in solvents such as alcohols, suggesting weak acidic nature of photoexcited DHHC. [52] From the experimental data, it was observed that the change in the acidity constant ~pKa* is about 1.2, suggesting a weak photoacidic character (equation 1) of DHHC.…”
Section: Water-assisted Excited State Proton Transfer (Espt)mentioning
confidence: 99%